The Effect of Bilingual Instruction to Students' Speaking Skill in SMPS PPM AL Ikhlash - Rahmita Irsani; Syarifuddin Dollah; Abdullah (International Journal of Language, Education, and Literature, 2024)
This research aimed to discover and comprehend students' perceptions regarding using bilingual instruction to teach speaking skills. This research used a quantitative approach with a pre-experimental design. The research population was nine grade students of SMPS PPM AL IKHLASH. The sample was 20 students as an experimental class. The researcher used the Speaking Test and students' perception questionnaire as the instruments of this research. Thus, this study showed that the results of frequency statistical calculations from 20 student respondents with positive perception criteria were 4 students (20%), and respondents with strongly positive perception criteria were 16 students (80%). It can be concluded that students have a positive perception of bilingual instruction. The results of this study can conclude that most students believe that bilingual instruction can improve speaking skills, and students also found it easier to communicate with their teachers and classmates when learning English.